Analysis Of BPJS Management Accounting Information System at Uptd Puskesmas Tegalbuleud Case Study of Tegalbuleud Public Health Center, Sukabumi Regency - Suratman Suratman; Acep Suherman; Tina Kartini (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
This study aims to determine: 1. To understand how to implement the BPJS management accounting information system at the UPTD Puskesmas Tegal Buleud. 2. To understand the BPJS management system in the Tegalbuleud Health Center UPTD program. 3. To understand the implementation of the BPJS management accounting information system at the Tegalbuleud Health Center UPTD. These variables consist of the accounting information system as the independent variable, and management as the dependent variable. The method used in this research is a qualitative method, the type of data used in this study is secondary data, namely data that is generated from the interview process and direct observation of the informant. Secondary data is obtained through the process of observation and interviews as well as data evidence in the form of documentation and data from the archives of the company where the research is carried out with the consideration of previous research. In this study, the data of the BPJS management accounting information system at the Tegal Buleud Health Center has been running quite well, the procedures, effectiveness, and the BPJS management information system used by the Tegal Buleud Health Center can be said to be quite effective and running well.